Penggunaan Hashtag Sebagai Varian promosi Produk Pada Media Sosial Instagram - Darniza Afriani; Dr. Mahyuzar Mahyuzar Drs, M.Si (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRAK- Penelitian ini berjudul “Penggunaan Hashtag Sebagai Varian Promosi Produk Pada Media Sosial Instagram”. Media sosial Instagram kini bukan hanya menjadi wadah untuk sekedar mengunggah foto namun juga menjadi sebagai media dalam memasarkan produk . Penelitian ini bertujuan untuk mengidentifikasi fenomena baru dalam dunia komunikasi pemasaran. Disini peneliti menggunakan model komunikasi pemasaran yaitu model marketing promotion mix . Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan analisis deskriptif. Pengumpulan data dilakukan dengan teknik wawancara semi terstruktur, observasi nonpartisipan dan dokumentasi. Wawancara tersebut dilakukan dengan menggunakan teknik purposive sampling, yaitu menentukan informan berdasarkan sejumlah kriteria yang telah ditentukan yaitu terhadap 5 orang informan yang merupakan pelaku bisnis online di Instagram dan menggunakan hashtag sebagai strategi mempromosikan produk. Berdasarkan hasil penelitian penggunaan hashtag sebagai strategi mempromosikan produk adalah sangat efektiv dan berefek pada peningkatan penjualan Kata Kunci : komunikasi pemasaran, Instagram, hashtag ABSTRACT - This research entitled "The Effectiveness of Product Promotion Through Social Media Instagram Using Hashtag". Social media Instagram is now not only a container to just upload photos but also become as a medium in marketing the product. This study aims to identify new phenomena in the world of marketing communications. Here the researcher uses a marketing communication model that is marketing promotion mix model. The method used in this research is qualitative approach with descriptive analysis. Data collection was done by semi-structured interview technique, nonparticipant observation and documentation. The interview was conducted by using purposive sampling technique, that is determining informants based on a number of predetermined criteria ie 5 informants who are online business in Instagram and using hashtag as a strategy to promote the product. Based on the results of research using the hashtag as a product promoting strategy is very effecve and has an effect on sales increase. Keywords: Marketing Communications, Instagram, hashtag ABSTRACT - This research entitled "The Effectiveness of Product Promotion Through Social Media Instagram Using Hashtag". Social media Instagram is now not only a container to just upload photos but also become as a medium in marketing the product. This study aims to identify new phenomena in the world of marketing communications. Here the researcher uses a marketing communication model that is marketing promotion mix model. The method used in this research is qualitative approach with descriptive analysis. Data collection was done by semi-structured interview technique, nonparticipant observation and documentation. The interview was conducted by using purposive sampling technique, that is determining informants based on a number of predetermined criteria ie 5 informants who are online business in Instagram and using hashtag as a strategy to promote the product. Based on the results of research using the hashtag as a product promoting strategy is very effecve and has an effect on sales increase. Keywords: Marketing Communications, Instagram, hashtag